Something about the sky - Carson, Rachel, 1907-1964 (Candlewick Studio, an imprint of Candlewick Press, 2024)
Rachel Carson once wrote, "It is not half so important to know as to feel." What do we know about clouds? There are three basic types: stratus, cumulus, and cirrus. Some are fleecy and fair-weathered while others portend storms. But clouds are more than pretty or ominous backdrops. They're the vehicle of water between sea and land, land and sea, in a cycle without end or beginning. They are the writing of the wind on the sky, a language all their own. An illustrator note explains the origins of Rachel Carson's shimmering essay--previously unpublished in its entirety--and the process of adapting it to picture book format, as well as how the author of Silent Spring forever changed the way we think about science and progress. Bringing the soft edges of clouds and the natural world to vivid life with a new, more fluid approach to her signature cut-paper technique, Nikki McClure inspires true emotional engagement with the world we all share. An antidote to "get your head out of the clouds," this art-meets-science tribute to curiosity and wonder is a gift for daydreamers and nature lovers of all ages.